ASSESSING THE IMPACT OF TECHNOLOGICAL SUPPORT ON TEACHERS’ JOB PERFORMANCE IN SECONDARY SCHOOLS IN IMO STATE - C, Chigbu, Baptista (Cuestiones de Fisioterapia, 2024)
This study assessed the impact of technological support and teachers’ job performance in secondary schools in Imo State. The study adopted a correlational survey design to analyse the relationship between technology use and teachers’ job performance. Four research questions and four hypothesis guided the study. The study population was five thousand, five hundred and twenty-four (5,524) secondary school teachers in Imo State. Purposive sampling was used to draw a sample of two hundred (200) teachers. Data were collected using a 24-item research questionnaire titled “Technological Support and Teachers’ Job Performance Questionnaire” (TSTJPQ). The collected data were analyzed using SPSS of descriptive and inferential analyses. Linear regression were used to answer research questions and t-test associated with linear regression was used to test the hypothesis at 0.05 level of significance. The results revealed that there is a significant positive correlation between technological support and teachers’ job performance. Specifically, teachers who use technological support tend to perform better on the job. The findings also highlighted the importance of motivation in mediating the relationship between technological support and job performance of secondary school teachers within the state. The findings of this study for school administrators and educators could improve teacher-student interaction, facilitates effective lesson planning, promotes teacher professional development, increases teacher job satisfaction, and improves teacher instructional delivery. The study recommended ways of enhancing technological support for secondary school teachers so as to enhance their job performance.